Menatap Fiqh Kedepan Dalam Merealisasikan Perbedaan Mazhab Menjadi Rahmat - Siti Nuraeni Mitra; Yurna Yurna (LP3M KH Yazid Karimullah Institute, 2023)
Ikhtilaf in this discussion is a difference of opinion among Islamic jurists in determining some Islamic laws that are furu' in nature, not on issues of ushul Islamic law, which are caused by differences in understanding or differences in methods in determining the law of a problem. Differences in sects can be a source of mercy (grace) and strengthen unity within Muslims. The futuristic approach to the different schools of thought fiqh involves several important aspects. First, a deep understanding of the universal basic principles of Islam, such as tolerance, compassion, and justice, is needed to overcome differences in sects. Second, constructive and respectful dialogue between religious thinkers from various schools of thought is the key to widening understanding and embracing differences. With this approach, Muslims can strengthen unity and build a harmonious environment capable of appreciating the rich diversity of Islamic traditions.